Overexpression of endothelial S1pr2 promotes blood–brain barrier disruption via JNK/c-Jun/MMP-9 pathway after traumatic brain injury in both in vivo and in vitro models - Cheng, Hongbo; Men, Yijiao; An, Yaqing; Yu, Jiegang; Zhang, Gengshen; Li, Jiaming; Wang, Xiaoliang; Sun, Guozhu; Wu, Yang (Frontiers in Pharmacology, 2024)
Objectives: The disruption of blood-brain barrier (BBB) is associated with poor outcomes of TBI patients. Sphingosine-1-phosphate receptor 2 (S1pr2), a member of the G protein-coupled receptor family, is involved in endothelial activation and the regulation of vascular integrity. We hypothesized that the inhibition of S1pr2 may alleviate BBB disruption and explored potential underlying molecular mechanisms.Methods: Lesion volumes were assessed utilizing Nissl staining; neurological outcomes were evaluated through a battery of neurobehavioral assessments; phenotypeassociated proteins were scrutinized via Western blot analysis; levels of reactive oxygen species (ROS), neuronal apoptosis, and S1pr2 expression were determined using immunofluorescence staining. The impact of S1pr2 inhibition after TBI and its underlying mechanism were elucidated using the selective S1pr2 inhibitor JTE-013, the JNK phosphorylation inhibitor SP600125, and cellular models. Chip-qPCR was employed to further elucidate the binding sites of the transcription factor c-Jun.Results: The expression of S1pr2 significantly increased following TBI in mice.Pharmacological inhibition of S1pr2 alleviated secondary injury with reduced lesion volume, ROS generation, cerebral oedema, neurological deficits, and neuronal apoptosis; BBB disruption was also mitigated, accompanied by reduced degradation of tight junction proteins and decreased induction of matrix metalloproteinases-9 (MMP-9) post-TBI. Mechanistically, TBI induces an increase in S1pr2 specifically in endothelial cells, leading to the promotion of MMP-9 transactivation by enhancing JNK/c-Jun signaling. This results in the degradation of tight junction proteins and increased BBB permeability. Through in vitro and in vivo Chip-qPCR experiments, we verified that AP-1a and AP-1b of MMP-9 promoter function as binding sites for phosphorylated c-Jun.Conclusions: Our findings identify a previously undisclosed role of S1pr2 in the pathophysiology of TBI. The S1pr2 inhibition presents a novel approach to alleviate BBB disruption after TBI through regulating the JNK/c-Jun/MMP-9 pathway.